2014
DOI: 10.14359/51687029
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Collapse Resistance Demand of RC Frames under Catenary Mechanism

Abstract: Progressive collapses are resisted by the catenary mechanism in reinforced concrete (RC) frame structures undergoing large deformations. Research to date has mainly focused on the nonlinear dynamic progressive collapse resistance demand of this type of structures under the beam mechanism (that is, for small deformations), and that the catenary mechanism is lacking. As a first attempt, this study establishes a dynamic amplification factor for evaluating the resistance demands of RC frames under the catenary mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Defining k = c s/2, the movement equation for the falling tile in the y-direction can be given as (3) After solving Equation 3, the trace of the tile in the y-direction can be calculated with Equation 4ln cosh /…”
Section: Physical Model Of Falling Tilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining k = c s/2, the movement equation for the falling tile in the y-direction can be given as (3) After solving Equation 3, the trace of the tile in the y-direction can be calculated with Equation 4ln cosh /…”
Section: Physical Model Of Falling Tilesmentioning
confidence: 99%
“…With the development of earthquake engineering, the earthquake-induced collapse of building structures has been effectively controlled in recent years [1][2][3][4][5][6]. However, seismic damage of indoor nonstructural components remains a serious issue, leading to possible occupant casualties.…”
Section: Introductionmentioning
confidence: 99%
“…As defined in this work, the beam or column sectional failure was reached upon the fracturing of all the steel fibers or the crushing of all the concrete fibers within that section, respectively. The RC beams exhibited bending and tensile capacities under small and large deformations, respectively, which contributed to the collapse resistance of the building [42][43][44]. Similarly, bending and compressive mechanisms also existed in the columns under small and large deformations, respectively.…”
Section: Component Failure Criteriamentioning
confidence: 93%
“…2. Based on a column removal scenario, Li et al 28 revealed that the progressive collapse resistance of an RC frame is largely dependent on the catenary mechanism of the frame beam. Further studies by Yu and Tan, 14 Qian et al, 15 Ren et al, 16 and Lu et al, 29 and indicated that the resistance of an RC beam under the catenary mechanism is dominated by the area of the continuously arranged longitudinal reinforcement.…”
Section: B the Proposed Detailing Techniquementioning
confidence: 99%